NICOLAI SINAI’S HISTORICAL-CRITICAL APPROACH TO THE QUR’AN: A CRITICAL STUDY OF LITERARY COHERENCE, CHRONOLOGY, AND INTERTEXTUALITY - Asyiq Billah Ali; Maulida Fitri Fi Ardillah; Huda Binti Mohd Fadzil; Fejrian Yazdajird Iwanebel (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2025)
This article examines the historical-critical approach developed by Nicolai Sinai in Quranic studies. The main focus includes three methodological dimensions: literary coherence and secondary revision, inner-Qur’anic chronology, and intertextuality. Through a qualitative library research method, this study explores how Sinai's approach offers an empirical and systematic alternative to traditional and earlier Western historical-critical methods that are often accused of undermining Islamic orthodoxy. Sinai’s contribution fills a significant gap in contemporary Qur’anic hermeneutics by bridging classical Islamic interpretive traditions and modern critical methodologies. His framework offers a more nuanced and respectful engagement with the Qur’anic text, avoiding reductionist tendencies while encouraging deeper philological and literary analysis. The study reveals how Sinai’s moderate historical-critical model, grounded in textual data, can enrich both Western and Islamic scholarship in understanding the historical development, structure, and intertextual dialogue of the Qur’an.